A survey of job satisfaction of UP interior design graduates - Acdal, Charisse Mae C.
The purpose of this study was to show the factors that affect the job satisfaction of interior design graduates with their choice of career whether it be strictly interior design, allied or non-allied jobs. It will give fresh graduates a glimpse of possible career options. A survey was conducted to gather information from U.P. interior design graduates from 1989 to 2006. Only 57 respondents of U.P. interior design graduates were surveyed using a mobile phone and through e-mail. The contact information retrieved was limited because some of the contact information were no longer updated and deemed unusable. The thesis utilized Maslow's hierarchy of needs assuming that these were motivational needs for Asians. Based on the findings of the study, it is apparent that interior design graduates are versatile because they can go to different jobs other than strictly venturing into the field of interior design. There are wide opportunities for interior design graduates where creativity can further be explored. Results show that interior design graduates are satisfied with their jobs because needs are addressed regardless of what career, they pursued be it strictly interior design, allied or non-allied jobs. There are a variety of factors that can influence a person's level of job satisfaction; some of these factors include the level of pay and benefits, the perceived fairness of the promotion system within a company, the quality of the working conditions, leadership and social relationships, and the job itself. All needs are moderately correlated to the overall satisfaction of graduates, based from Maslow's hierarchy of needs. It is observed from the study that the field they pursued has no relation to one's job satisfaction because salary is a major contributor to one's satisfaction in his or her career.